Five Minutes a Day to Improve Comprehension Monitoring in Oral Language Contexts: An Exploratory Intervention Study With Prekindergartners From Low-Income Families. Issue 4 (October 2016) - Kim, Young-Suk Grace; Phillips, Beth
Abstract : Comprehension monitoring has received substantial attention as a reading comprehension strategy. However, comprehension monitoring is not limited to the reading context, but applies to the oral context for children's listening comprehension, which is a critical foundation for reading comprehension. Therefore, a systematic and explicit instructional routine for comprehension monitoring in oral language contexts was developed for prekindergartners from low-income families. Instruction was provided in small groups for approximately 5 min a day for 4 days a week for 8 weeks. Results showed that children who received comprehension monitoring instruction were better at identifying inconsistencies in short stories than those who received typical instruction with a medium effect size ( d = .57). These results suggest comprehension monitoring is malleable and can be taught in the oral language context to prereaders from low socioeconomic backgrounds. Furthermore, the instructional routine reported in this study is flexible for individual, small group, or whole class settings, and likely can be easily delivered by educators such as teachers and paraeducators.